PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MINUMAN PADA ECCHOFEE - Ronaldo Dwi Saputro (2023)
This type of research conducted by researchers is a quantitative study that aims to determine the effect of product quality, service quality, promotion, and purchasing decisions on ecchofee. This study used a sample of 92 respondents from the population in East Jakarta who made purchases at Ecchofee. The sampling technique uses non-probability sampling using a purposive sampling method. The data collection carried out in this study used an online questionnaire using the Google Form which was then distributed via the Line, WhatsApp, Twitter, Instagram and Telegram applications. This study uses the PLS (Partial Least Square) analysis technique with the SmartPLS 3.0 application. The results obtained from this study are: (1) The product quality variable has a positive and significant effect on purchasing decisions with a path coefficient value of 0.341. (2) The service quality variable has a positive and significant effect on purchasing decisions with a path coefficient value of 0.217. (3) The promotion variable has a positive and significant effect on purchasing decisions with a path coefficient value of 0.360.